Pemberdayaan Masyarakat Karibia melalui Pelatihan Pengolahan Mango Jelly dan Pemanfaatan Limbah Mangga - Irna Ekawati; Maryam; Khairun Nadiyah; Adlina Safitri Helmi; Khairul Akli; Ester Edwar; Lisa Nesti; Dian Hasni; Eko Supriadi (JICE : Journal of Industrial Community Empowerment, 2025)
The Caribbean region, despite its abundance of tropical agricultural commodities such as mangoes, continues to face challenges in product diversification and value-added processing. This community engagement program aimed to strengthen the productive capacity and economic empowerment of Caribbean communities—particularly small-scale farmers, agroindustry actors, and homemakers—through mango-based product development. Implemented by Politeknik ATI Padang in collaboration with the Non-Aligned Movement Center for South-South Technical Cooperation (NAM-CSSTC), the program was conducted virtually over two days in May 2025 using an integrated explicit–tacit knowledge transfer approach. Explicit knowledge was delivered through structured digital materials and video-based instruction, while tacit knowledge was reinforced through experiential learning, practical assignments, and interactive discussions. A total of 297 participants enrolled for the program, with 30 participants actively engaging through Zoom sessions and 267 participants accessing the training via YouTube livestreaming. The primary outcomes of the program included measurable improvements in participants’ technical competence, production readiness, and sustainability awareness. Evaluation results showed an increase in participants’ average scores from 84.4 (pre-test) to 89.2 (post-test), indicating enhanced understanding of mango jelly processing, packaging, waste utilization, and basic business planning. Moreover, participants successfully demonstrated their ability to independently produce mango jelly and apply organic waste management practices using mango peel residues. Beyond skill acquisition, the program fostered entrepreneurial motivation and promoted the adoption of circular economy principles at the community level. These findings highlight the effectiveness of virtual community empowerment initiatives in achieving tangible capacity-building outcomes and supporting sustainable, resource-based economic development across geographically dispersed regions.